District level value-added dynamical-synoptic forecast system for rainfall
Lkkj & bl ’kks/k&Ik= esa o"kkZ ls lacaf/kr ftyk Lrjh; ekuksa ij vk/kkfjr xfrdh; flukfIVd iwokZuqeku dh Ik)fr vkSj mlds iz;ksxkRed ifj.kkeksa dks izLrqr fd;k x;k gSA blds igys bl rduhd dk mi;ksx o"kZ 2005 dh ekulwu iwoZ dh _rq] nfk.kh if’peh ekulwu _rq vkSj ekulwu ds Ik’pkr dh _rq ds nkSjku gqbZ ftysokj o"kkZ dk iwokZuqeku yxkus ds fy, fd;k x;k FkkA mDr 2005 ds iwokZuqeku ds fy, Vh-&80],e- ,e- 5] jk"Vªh; e/; vof/k ekSle iwokZuqeku dsUnz ¼,u- lh- ,e- vkj- MCY;w- ,Q-½ ds- bZ- Vh- ,- vkSj Hkkjr ekSle foKku foHkkx esa dk;Z’khy ,e- ,e- 5 xfrdh; fun’kksZa dk lefUor #Ik ls mi;ksx fd;k x;k FkkA iwokZuqeku esa lefUor #Ik ls ;ksxnku nsus okys lHkh fun’kksZa ds ekuksa dk vyx&vyx ewY;kadu djds muls izkIr gq, o"kkZ ds iwokZuqekuksa dk mi;ksx djds xfrdh; iwokZuqeku rS;kj fd;k x;k gSA ifjpkyu yk.kksa] m/okZ/kj osx] mixzg ls izkIr lwpuk flukfIVd pkVksZa vkSj tyok;q foKku vkfn tSls vU; fun’kksZa dk vkdyu djds xfrdh; iwokZuqekuksa dks eku vk/kkfjr ¼osY;w ,fMM ½ flukfIVd ekSle iwokZuqekuksa esa ifjofrZr fd;k x;k gSA o"kZ 2005 esa fd, x, iwokZuqeku ds vuqHko ls ;g irk pyk gS fd lefUor #Ik ls ;ksxnku nsus okys fun’kksZa ls vyx&vyx izkIr gq, o"kkZ ds iwokZuqekuksa dh fuiq.krk dh rqyuk esa eku&vk/kkfjr ¼osY;w ,fMM ½ xfrdh; flukfIVd iz.kkyh ds 24, 48, 72 ?kaVksa ds ftyk Lrjh; o"kkZ ds iwokZuqeku dgha vf/kd fuiq.krk ls rS;kj fd, tk ldrs gSaA The paper presents the methodology and trial results of the district level value-added dynamical-synoptic forecast for rainfall. The technique was tried for forecasting districtwise rainfall during Pre-monsoon, Southwest Monsoon and Post monsoon seasons of 2005. The constituent dynamical models were T-80, MM5, ETA of the National Centre for Medium Range Weather Forecasting (NCMRWF) and the MM5 model operational at India Meteorological Department, New Delhi. The dynamical predictions were prepared using the rainfall predictions of the constituent models by assigning different weights. The dynamical predictions were converted into value-added synoptic-weather forecasts by taking into account other inputs like circulation features, vertical velocity, satellite information, synoptic charts and climatology etc. The experience during 2005 has shown that the value-added dynamical-synoptic system can produce 24, 48, 72 hours district level rainfall forecast of greater skill than the skills of the constituent models. , number=2, journal=MAUSAM, author=LAL, B. and SINGH, O. P. and PRASAD, ONKARI and BHOWMIK, S. K. ROY and KALSI , S. R. and SUBRAMANIAN, S. K., year=2006, month=Apr., pages=209–220